2017
DOI: 10.1097/coh.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

Current assessment of heart rate variability and QTc interval length in HIV/AIDS

Abstract: These emergent studies support the clinical relevance of the ECG across the age and HIV disease spectrum. Furthermore, the reported findings have implications for the management of cardiovascular and chronic inflammatory disease comorbidity in persons living with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…HIV and pathologic Q-waves were associated in univariable analyses, but this association was attenuated to borderline significance after adjusting for traditional risk factors, suggesting an adverse risk profile among PLWH 9,24 to contribute. PLWH have increased risk of heart failure and cardiomyopathies 12 , and studies of intraventricular conduction defects in PLWH have found QRS-duration to be associated with use of protease inhibitors 25 . We therefore hypothesized HIV infection to be associated with IV-block, but distribution of IV-blocks was similar in PLWH and controls and there was no association to specific cART regimens.…”
Section: Discussionmentioning
confidence: 99%
“…HIV and pathologic Q-waves were associated in univariable analyses, but this association was attenuated to borderline significance after adjusting for traditional risk factors, suggesting an adverse risk profile among PLWH 9,24 to contribute. PLWH have increased risk of heart failure and cardiomyopathies 12 , and studies of intraventricular conduction defects in PLWH have found QRS-duration to be associated with use of protease inhibitors 25 . We therefore hypothesized HIV infection to be associated with IV-block, but distribution of IV-blocks was similar in PLWH and controls and there was no association to specific cART regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ART-naïve HIV+ individuals from developing countries suggest an increased prevalence of QT prolongation compared with HIV− controls and support a significant direct HIV effect 12. Among persons on ART, prior studies suggest longer QT intervals in those taking older PIs and NNRTIs 11.…”
Section: Discussionmentioning
confidence: 96%
“…Electrocardiogram (ECG) was demonstrated to be another rational method to predict the cardiotoxicity of drugs 89 . Very recently, our group investigated the cardiac toxicity of 12 (Figure 5) by the ECG 29 .…”
Section: Safety Inspectionmentioning
confidence: 99%